The Utilization of Microsoft Excel in Accounting to Improve the Accuracy of Financial Reporting in the Digital Era - Nailah Airin Nur Fadillah; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Financial reporting is a fundamental component of business management because it provides information regarding an entity's financial position, performance, and cash flows. However, many Micro, Small, and Medium Enterprises (MSMEs) in Indonesia continue to encounter challenges in preparing accurate financial statements that comply with applicable accounting standards. This study aims to examine the utilization of Microsoft Excel in accounting practices to improve the accuracy of financial reporting in the digital era. The study employed a systematic literature review by analyzing relevant scholarly publications concerning digital accounting, Microsoft Excel, financial reporting, and MSMEs. The findings indicate that Microsoft Excel enhances the accounting process by reducing manual recording errors, supporting systematic bookkeeping, and facilitating the preparation of more accurate and reliable financial statements. Spreadsheet features, including automated formulas, data validation, lookup functions, and Pivot Tables, contribute to improving data processing efficiency, reporting consistency, and compliance with Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The study concludes that Microsoft Excel represents an affordable and practical digital accounting solution that supports financial reporting quality while facilitating the gradual digital transformation of MSMEs that have not yet adopted specialized accounting software.